Social networks and gender inequitable attitudes among men and women in rural Nepal - Shweta Tomar; Cari Jo Clark; Abbie Shervinskie; Gemma Ferguson; Holly Baker Shakya (Taylor & Francis Group, 2024)
Gender-inequitable attitudes are known factors associated with women's experience of intimate partner violence (IPV). The current study aims to identify social network factors associated with gender-inequitable attitudes among men and women in Nepal. Data came from the baseline assessment for evaluating Change Starts at Home- an IPV prevention intervention in rural Nepal (N = 1994). Linear regression models adjusted for participant demographics provided the associations between participants' gender-inequitable attitude scores (GIAS) and their social network characteristics. Results show that women who nominated their parents (beta = −1.29) or neighbours (beta = −1.18) had better GIAS while those nominating their brother-in-law/sister-in-law (beta = 0.36) had worse GIAS. Men with higher degree (beta = −0.27) and those who nominated their spouse (beta = −0.75) had better GIAS. Women's GIAS was strongly associated with their alters' when the alter was within their household, had a closer relationship, or the alter was male. Men's GIAS was strongly associated with their alters' attitudes when the alter was not from the same household or if they had a weak tie. Findings indicate that IPV prevention programmes must consider men's and women's network characteristics separately. For example, interventions for women should focus on relationships within their households, while interventions for men should focus on relationships outside their households.